The The Implementation of Robinson’s Strategy (SQ3R) to Enhance The Reading Ability in English Class: Pengimplementasian Strategi Robinson (SQ3R) untuk Meningkatkan Kemampuan Reading di Kelas Bahasa Inggris - Muhammad Galuh Elga Romadhon (UICELL, 2020)
Abstract: This article is arranged to review and compare the theory about implementing of Robinson's strategy (SQ3R) to enhance reading prowess in English context. As we know that reading is the imperative skill at various academic levels. In reading activities, especially reading English texts, lack of motivation is a serious problem faced by students. This can be influenced for the students’ interest in reading activity. Besides, the limited time in reading activity can be the problems when the students in reading class. Furthermore, lack of vocabulary can be the obstacle for the students to understand and acquire the information during they read the English text. To solve these difficulties, we need to find a strategy that can be applied to the students in enhancing their reading. One of the strategy that can be used to solve the problems is utilizing SQ3R (Survey, Question, Read, Recite, and Review) strategy. In this article, the writer would review and discuss about the theory of SQ3R as the reading strategy, the mechanism of this theory, the advantages and the challenges, and also the previous study. This article will be closed with the conclusion and recommendation to apply SQ3R as the strategy in reading class.